La ecología cósmica de Ernesto Cardenal - Edgar Romero (Caravelle)
The poetry of the Nicaraguan Ernesto Cardenal (1925-2019) is eminently focused upon the world. The current ecological crisis could’nt be absent from his Cántico cósmico (1989), a long poem that dwells on the ecological problems’ very high human cost caused by the capitalist mode of production and whose ecosystemic approach expands and finally connects with the other great theme of Cardenal’s poetry: the search for a mystical communion with the others as well as with the cosmos.